2016
DOI: 10.1016/j.camwa.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Implementation issues and benchmarking of lattice Boltzmann method for moving rigid particle simulations in a viscous flow

Abstract: a b s t r a c tIn this work, we revisit implementation issues in the lattice Boltzmann method (LBM) concerning moving rigid solid particles suspended a viscous fluid. Three aspects relevant to the interaction between flow of a viscous fluid and moving solid boundaries are considered. First, the popular interpolated bounce back scheme is examined both theoretically and numerically. It is important to recognize that even though significant efforts had previously been devoted to the performance, especially the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 54 publications
2
84
0
1
Order By: Relevance
“…It is clear that the GME results are more accurate and far steadier than the ALD and LME results. Peng et al [62] confirmed the computational accuracy and Galilean invariance of GME by theoretical analyses and numerical simulations. investigate the influences of Reynolds number, we perform a set of simulations in which the particle densities increase from 1.02 to 1.22 g/cm 3 , and the corresponding Reynolds number grows gradually from 6.13 to 34.75.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…It is clear that the GME results are more accurate and far steadier than the ALD and LME results. Peng et al [62] confirmed the computational accuracy and Galilean invariance of GME by theoretical analyses and numerical simulations. investigate the influences of Reynolds number, we perform a set of simulations in which the particle densities increase from 1.02 to 1.22 g/cm 3 , and the corresponding Reynolds number grows gradually from 6.13 to 34.75.…”
supporting
confidence: 50%
“…It is clear that the GME results are more accurate and far steadier than the ALD and LME results. Peng et al [62] confirmed the computational accuracy and Galilean invariance of GME by theoretical analyses and numerical simulations. …”
supporting
confidence: 50%
See 1 more Smart Citation
“…The missing distribution functions for the new fluid lattice node are constructed by a new velocityconstrained extrapolation method to be discussed below (section 2.2). The hydrodynamic force F i and torque Γ i acting on the i th particle are calculated during the interpolated bounce-back procedure by the recentlydeveloped Galiean invariant momentum exchange method [39,40]. It is very important that we enforce the local Galilean invariance property in order to produce physically correct results, as discussed in Peng et al [40].…”
Section: The Lattice Boltzmann Methods (Lbm)mentioning
confidence: 99%
“…This then requires the restoring of the missing distribution functions f q , which can be achieved by setting them to their equilibrium value based on a local average density or by extrapolating them from the body's normal direction, see e.g. [4]. All restoration algorithms must satisfy the constraint that the fluid velocity in these cells has to match the body's surface velocity at this position.…”
Section: Numerical Algorithmmentioning
confidence: 99%